First Demonstration of Ge2Sb2Te5-Based Superlattice Phase Change Memory with Low Reset Current Density (-3 MA/cm2) and Low Resistance Drift (-0.002 at 105°C) - Intisar Khan, Asir; Perez, Christopher; Wu, Xiangjin; Won, Byoungjun; Kim, Kangsik; Kwon, Heungdong; Ramesh, Pranav; Neilson, Kathryn M.; Asheghi, Mehdi; Saraswat, Krishna; Lee, Zonghoon; Oh, Il Kwon; et al. (Digest of Technical Papers - Symposium on VLSI Technology, 2022)
Superlattice (SL) heterostructures have shown promise to reduce the reset current density (Jreset) and resistance drift coefficient (v) of phase change memory (PCM). However, SLs have not been studied with the well-known phase change material Ge2Sb2Te5 (GST), and the effect of SL interfaces and intermixing layers also remains unknown. Here, using SLs based on GST/Sb2Te3 for the first time, we simultaneously achieve Jreset ˜ 3-4 MA/cm2 and 7 resistance states (v ˜ 0.002) in mushroom-cell PCM with bottom electrode diameter down to 110 nm. The low Jreset and v are retained even after 106 cycles and at high temperature (105°C), respectively. We also uncover that both Jreset and v in SL-PCM decrease with increasing number of SL interfaces - but SL intermixing increases both, also showing up as evidence in thermal conductivity and X-ray diffraction measurements. This study advances SL-PCM technology for high-density storage and neuromorphic applications.
Keywords: Drift coefficient; Ge2Sb2Te5; Interface layer; Intermixing layer; Low reset currents; Low resistance; Phase-change memory; Reset currents; Resistance drifts; Resistance state